Efficacy and short-term side effects of sitagliptin, vildagliptin and saxagliptin in Chinese diabetes: a randomized clinical trial. Issue 4 (April 2019) - Zhou, Xiao-jun; Ding, Lin; Liu, Jia-xin; Su, Le-qun; Dong, Jian-jun; Liao, Lin
Abstract : Aims: To investigate the difference in the efficacy among dipeptidyl peptidase-4 (DPP-4) inhibitors in Chinese adults with newly diagnosed diabetes. Materials and methods: In a multicenter, randomized study, we enrolled adults who were either treatment naive or off prior anti-hyperglycemic therapy for at least 3 months. Eligible patients had hemoglobin A1c (HbA1c) concentrations of 6.5–9.5%. Three hundred patients had been randomly allocated to sitagliptin 100 mg, once daily; vildagliptin 50 mg, twice daily and saxagliptin 5 mg, once daily for 12 weeks. Patients and investigators were masked to treatment assignment. The primary endpoint was change from baseline in HbA1c at week 12. This study was completed and registered with ClinicalTrials.gov, number NCT 01703637. Results: Totally 277 patients were enrolled in the final analysis, and 93 patients received sitagliptin, 94 received vildagliptin and 90 received saxagliptin. Compared with baseline, adjusted mean differences in change from baseline HbA1c at week 12 were −0.50% (95% CI: −0.20 to −0.90), −0.65% (95% CI: −0.40 to −1.40), −0.70 (95% CI: −0.50 to −1.00) for sitagliptin, vildagliptin and saxagliptin group, respectively. The overall HbA1c-lowering effect was similar for all three selected DPP-4 inhibitors after adjustment for age and baseline HbA1c. Notably, in secondary outcome analysis, patients in vildagliptin group showed a significant decrease in total cholesterol levels, compared with participants in sitagliptin and saxagliptin groups. No significant between-group difference was shown in adverse events (AE). Conclusions: The overall HbA1c-lowering effect and incidence of AE were similar for sitagliptin, vildagliptin and saxagliptin in Chinese adults with newly diagnosed diabetes.